Failure Behaviour of Sandstone with a Preexisting Joint under Stepped Excavation - Yinzhu Liu; Ping Cao; Liwen He; Qibin Lin (Advances in Civil Engineering)
Much geotechnical construction needs to be carried out under the condition of stepped excavation. However, there is still a lack of research on crack coalescence and failure modes of jointed rock mass under stepped excavation conditions. In order to simulate the stepped excavation test of the real project, the polylactic acid (PLA) material is selected as the filler for the excavation area. The stepped excavation tests are performed on sandstone specimens containing a preexisting joint under different normal load conditions. The dynamic stepped excavation of simulating excavate rock engineering is realised. The constant normal loads during the excavation process are determined to be 80 kN and 100 kN. The influence of the joint inclination on the failure characteristics of the excavation process is analysed. Four typical failure modes are summarised: (a) Mode I: crack coalescence of tensile failure; (b) Mode II: crack coalescence of mixed failure; (c) Mode III: without crack coalescence of mixed failure; (d) Mode IV: without crack coalescence of shear failure. Furthermore, the failure characteristics of the area above the excavation hole and the preexisting joint are analysed. The results show that there are three failure modes: (a) Type I: spalling failure; (b) Type II: shear slip failure; (c) Type III: shear slip and spalling mixed failure.